Java Language Maintenance In Mun - Jaya, Rajabindra; Hanna, Hanna; Suhartini, Lelly (Universitas Halu Oleo, 2021)
This research discussed Java language maintenance by Javanese people living at Bangunsari, Muna. It focused on condition in several domains as family, school, neighbourhoods, mosque, and mass media as well as the researcher reviewed in terms of age groups, and causal factors leading to the language maintenance. The data were interview and conversation with the Javanese people at Bangunsari. Design used was qualitative research through ethnography approach. The researcher used observation, recording, and interview as the instruments to get data. The result showed that Javanese people who lived at Bangunsari village more frequently used Java language in their daily life. In the domain of family, Javanese people were monolingual as personally, bilingual with code mixing and code switching as well as in the domain of neighbourhoods. As in the domain of school, they personally were qualified as monolingual speakers with code switching. Religion domain showed that the Javanese people personally were qualified as monolingual speakers with code mixing in bilingual situation as well as in groups of age in 10 up to 50 years old and above still used Java language even though they mixed or switched into bahasa. The causal factors that lead the language maintenance of Java language were number of speakers, loyalty and awareness of Java language, continuity of Java language usage, and the power of Java language and other factors reviewed from sociolinguistic perspectives such as population mobility, culture and tradition, education, and religion.